Population development in South-West Saxony and resulting consequences - Jurczek, Peter (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
For several years, Germany has been characterised by a declining population development. Regions in eastern Germany are especially affected by this as the example of South-western Saxony will show. Main cause of this development is the constantly declining birth rate which effects are strengthened by a negative migration rate. Statistic prognoses for the year 2015 do now show an improving situation but rather forecast an intensification of population losses, although with regional differences. The tendentiously further declining number of population causes numerous and diverse effects that influence social life in general but also induce special consequences. Therefore, action-oriented strategies have to be developed and implemented to secure the number and structure of population. They include several fields of special measures.